Recent progress in analytical capillary isotachophoresis. Issue 1 (21st October 2014) - Malá, Zdena; Gebauer, Petr; Boček, Petr; El Rassi, Ziad
<x xml:space="preserve">Abstract</x> This paper brings a survey of papers on analytical capillary ITP published since 2012 until the first quarter of 2014. These papers are ranged according to their nature, the techniques used, and the instrumentation employed. The sequence of the related chapter titles is as follows: Theory and simulations, techniques and instrumentation, single‐column and column‐switching applications of ITP, ITP in microfluidic systems, on‐line ITP‐CZE and transient ITP (tITP) techniques and applications. The review shows the position of analytical capillary ITP among contemporary separation techniques and implies the potential future trends.